The Effect of Unilateral Spinal Anaesthesia and Psoas Compartment with Sciatic Block on the Postoperative Pain Management in Total Knee Artroplastic Surgery - Ebru Canakci; Dogus Unal; Yunus Guzel (Pain Research and Management)
Purpose. This study was designed to investigate the effects of peripheral nerve block methods, applied through unilateral spinal anaesthesia on elderly patients to undergo total knee arthroplasty, on perioperative hemodynamic parameters and postoperative analgesia period. Materials and Method. 60 patients were randomly divided into two groups in the study. In group USA spinal anaesthesia was performed. In group PCS it was applied on psoas compartment block and sciatic nerve block. Results. Significantly higher intraoperative 60th and 90th minute mean arterial pressure values were ascertained in the PCS group compared to the USA group. The decrease observed in the 5th, 10th, and 20th minute MAP values in the USA group was statistically significant according to the control MAP value. Concerning within group comparisons, the decrease in 5th, 10th, and 20th minute heart rate values in the USA group was statistically significant compared with the control measurement value. The mean beginning time of sensory and motor blocks in the PCS group was found to be at a significantly advanced level compared with that in the USA group. Conclusions. The PCS block technique using bupivacaine hydrochloride ensured a higher haemodynamic efficiency in the perioperative period in high-risk elderly patients undergoing total knee arthroplasty. This trial is registered with ClinicalTrials.gov Identifier: NCT03021421.